Pelatihan Peningkatan Kualitas Publikasi Penelitian Bagi Mahasiswa Doktoral di Universitas Negeri Semarang - Wijaya, Angga Pandu; Pramono, Suwito Eko (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2023)
Community service aims to provide assistance to doctoral students through research article writing seminars. The purpose of this service is to enhance the understanding and skills of doctoral students in writing high-quality research articles that meet academic standards. The methods employed in this service include organizing seminars on research article writing, in which doctoral students participate. The seminars cover various important aspects of research article writing, such as article structure, introduction writing, theoretical frameworks, research methodologies, data analysis, and conclusions. Additionally, evaluation criteria and practical tips for producing quality articles are also discussed. The results of this community service indicate that the research article writing seminars offer significant benefits to doctoral students. Participants enhance their understanding of the essential components of research article writing and have the opportunity to discuss and exchange ideas with fellow doctoral students and experienced speakers